2016
DOI: 10.1039/c6cp05233a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of helium at a Y2Ti2O7 nanocluster embedded in a BCC Fe matrix

Abstract: Nanostructured ferritic alloys (NFAs) are prime candidates for structural and first wall components of fission and fusion reactors. The main reason for this is their ability to effectively withstand high concentrations of the transmutation product helium. A high number density of oxide nanoclusters dispersed throughout a BCC Fe matrix act as trapping sites for helium and prevent its eventual delivery to high risk nucleation sites. The current study uses density functional theory to investigate the helium trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…It was found that a variety of possible cluster structures with similar energetics may exist: different cage configurations obtained by SM, AS, and PD models as well as configurations with oxygen in the center found after relaxation of SM-OC, AS-OC, and PD-OC models. This contradicts the opinion in recent theoretical literature that favors the SM model [11,36,37]. Furthermore, the role of Ti was investigated by comparing results for O-v-Y and O-v-Y-Ti clusters, and the binding of oxygen monomers to the clusters was studied.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It was found that a variety of possible cluster structures with similar energetics may exist: different cage configurations obtained by SM, AS, and PD models as well as configurations with oxygen in the center found after relaxation of SM-OC, AS-OC, and PD-OC models. This contradicts the opinion in recent theoretical literature that favors the SM model [11,36,37]. Furthermore, the role of Ti was investigated by comparing results for O-v-Y and O-v-Y-Ti clusters, and the binding of oxygen monomers to the clusters was studied.…”
Section: Discussionmentioning
confidence: 75%
“…The results of the present work have consequences for the interpretation of the role of the oxide nanoclusters regarding He storage. Previous investigations [37,38] only considered cage-like SM clusters as discussed in the work of Barnard et al [11]. These authors found that the most stable He site is inside the cage of the SM cluster followed by interstitial sites at the cluster-iron interface and the tetrahedral interstitial site in bcc Fe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, due to the oxidation that likely occurred during the hydriding step of the process, the He sequestration effects of the multilayers is diminished. However, He trapping at metal-metal oxide interfaces was shown to be an effective way to manage He inventory, such as in ODS [58][59][60]. DFT simulations showed the propensity for He to bind to Er oxide [61].…”
Section: Discussionmentioning
confidence: 99%
“…Another characterization of the interaction of mHe with the cluster is possible via the incorporation, solution or formation energy [22]…”
Section: Dft Calculationsmentioning
confidence: 99%
“…For this purpose, these authors considered supercells with planar interfaces between Y 2 O 3 or Y 2 Ti 2 O 7 and bcc Fe. Sun et al [21] investigated the interaction of one or more He atoms with a cubic O-Y cluster model in bcc Fe while Danielson et al [22] considered the incorporation of a single He atom into the O-Y-Ti cluster model of Barnard et al [23]. The O-Y models of Sun et al [21] and Barnard et al [23] are based on the atomic structures of Y 2 O 3 and Y 2 Ti 2 O 7 , respectively.…”
Section: Introductionmentioning
confidence: 99%